Informed consent for genomic research in the context of precision medicine. Ethical issues (BioLaw Journal - Rivista di BioDiritto, 2023)
The collection/generation of genomic data as well as their use in research raises a series of ethical issues related in particular to informed consent. Main ethical challenges, particularly incidental findings, privacy and the blurring line among research and therapy, are discussed in the contribution showing the implications for the informed consent and making reference to the indications in this regard of the National Bioethics Committee.
Keywords: genomic research; precision medicine; informed consent; incidental findings; genetic counseling